A review of split liver transplantation with full right/left hemi-liver grafts for 2 adult recipients. Issue 39 (1st October 2021) - Chan, Kun-Ming; Hung, Hao-Chien; Lee, Jin-Chiao; Wu, Tsung-Han; Wang, Yu-Chao; Cheng, Chih-Hsien; Lee, Chen-Fang; Wu, Ting-Jung; Chou, Hong-Shiue; Lee, Wei-Chen
Abstract : Abstract: Liver transplantation has become a routine operation in many transplantation centers worldwide. However, liver graft availability fails to meet patient demands. Split liver transplantation (SPLT), which divides a deceased donor liver into 2 partial liver grafts, is a promising strategy for increasing graft availability for transplantation and ameliorating organ shortage to a certain degree. However, the transplantation community has not yet reached a consensus on SPLT because of the variable results. Specifically, SPLT for 2 adult recipients using full right/left hemi-liver grafts is clinically more challenging in terms of surgical technique and potential postoperative complications. Therefore, this review summarizes the current status of SPLT, focusing on the transplantation of adult recipients. Furthermore, the initiation of the SPLT program, donor allocation, surgical aspects, recipient outcomes, and obstacles to developing this procedure will be thoroughly discussed. This information might help provide an optimal strategy for implementing SPLT for 2 adult recipients among current transplantation societies. Meanwhile, potential obstacles to SPLT might be overcome in the near future with growing knowledge, experience, and refinement of surgical techniques. Ultimately, the widespread diffusion of SPLT may increase graft availability and mitigate organ donation shortages.